2009
DOI: 10.1097/cad.0b013e32832a2dc1
|View full text |Cite
|
Sign up to set email alerts
|

Administration of reduced glutathione in FOLFOX4 adjuvant treatment for colorectal cancer: effect on oxaliplatin pharmacokinetics, Pt-DNA adduct formation, and neurotoxicity

Abstract: Oxaliplatin is a promising drug for cancer therapy and the oxaliplatin/5-fluorouracil/leucovorin (FOLFOX) regimen has become the standard adjuvant treatment for colorectal cancer. However, the oxaliplatin-induced neurotoxicity still represents a clinical problem leading to a discontinuation of the therapy. Many strategies have been proposed in order to manage the neurotoxicity, but their effect on antitumoral efficacy is still unclear. In this study, we investigated the effect of reduced glutathione administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
4
46
1
Order By: Relevance
“…Calcium and magnesium infusions were shown to decrease the incidence of oxaliplatin-induced neuropathy in a retrospective cohort study[21] and a smaller randomized placebo-controlled study[22], but these results have yet to be confirmed in a phase III study. Multiple clinical trials suggest that glutathione may decrease the severity of CIPN[2325], but again, these results have not been confirmed in a large trial. Small studies have identified other possible treatments for CIPN including the selective serotonin norepinephrine reuptake inhibitor, venlafaxine[26,27], the anti-epileptic drug, pregabalin[28], α-lipoic acid[29,30], and acetyl L-carnitine[31].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium infusions were shown to decrease the incidence of oxaliplatin-induced neuropathy in a retrospective cohort study[21] and a smaller randomized placebo-controlled study[22], but these results have yet to be confirmed in a phase III study. Multiple clinical trials suggest that glutathione may decrease the severity of CIPN[2325], but again, these results have not been confirmed in a large trial. Small studies have identified other possible treatments for CIPN including the selective serotonin norepinephrine reuptake inhibitor, venlafaxine[26,27], the anti-epileptic drug, pregabalin[28], α-lipoic acid[29,30], and acetyl L-carnitine[31].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the treatment would likely be best given throughout the full duration of the prescribed chemotherapy or only proximal to each chemotherapy infusion depends on the proposed mechanism and mode of administration of the investigational drug. For example, a bolus intravenous dose of an anti-inflammatory or other agent hypothesized to prevent nerve damage may be best administered directly before or after each chemotherapy infusion as was performed in multiple studies [102,104,113,141,155]. In fact, daily infusions of an investigational prophylactic CIPN treatment throughout the full course of chemotherapy are not likely to be feasible.…”
Section: Design Considerations In the Context Of 4 Illustrative Prmentioning
confidence: 99%
“…Witschi et al administered a single oral dose of up to 3 g of GSH to seven healthy subjects and did not observe an increase in blood GSH levels, concluding ''it is not feasible to increase circulating GSH to a clinically beneficial extent by the oral administration of 3 g of GSH.'' 22 Yet three studies have evaluated the impact of reduced GSH supplementation combined with oxidative chemotherapeutic agents in patients with various cancers [23][24][25] ; all three trials demonstrated reduced adverse effects of the chemotherapy without negative effects on the effectiveness of the regimen, suggesting some physiologic effect from oral dosing. Unfortunately GSH status was not measured in any of these trials.…”
Section: Introductionmentioning
confidence: 99%